The action of enhancing weak light capture via phototropic growth and chloroplast movement in plants - Xin, Guang-yuan; Li, Lu-ping; Wang, Peng-tao; Li, Xin-yue; Han, Yuan-ji; Zhao, Xiang (Stress biology, 2022)
To cope with fluctuating light conditions, terrestrial plants have evolved precise regulation mechanisms to help optimize light capture and increase photosynthetic efficiency. Upon blue light-triggered autophosphorylation, activated phototropin (PHOT1 and PHOT2) photoreceptors function solely or redundantly to regulate diverse responses, including phototropism, chloroplast movement, stomatal opening, and leaf positioning and flattening in plants. These responses enhance light capture under low-light conditions and avoid photodamage under high-light conditions. NON-PHOTOTROPIC HYPOCOTYL 3 (NPH3) and ROOT PHOTOTROPISM 2 (RPT2) are signal transducers that function in the PHOT1- and PHOT2-mediated response. NPH3 is required for phototropism, leaf expansion and positioning. RPT2 regulates chloroplast accumulation as well as NPH3-mediated responses. NRL PROTEIN FOR CHLOROPLAST MOVEMENT 1 (NCH1) was recently identified as a PHOT1-interacting protein that functions redundantly with RPT2 to mediate chloroplast accumulation. The PHYTOCHROME KINASE SUBSTRATE (PKS) proteins (PKS1, PKS2, and PKS4) interact with PHOT1 and NPH3 and mediate hypocotyl phototropic bending. This review summarizes advances in phototropic growth and chloroplast movement induced by light. We also focus on how crosstalk in signaling between phototropism and chloroplast movement enhances weak light capture, providing a basis for future studies aiming to delineate the mechanism of light-trapping plants to improve light-use efficiency.